2023
DOI: 10.5603/cj.a2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Elective cardioversion of atrial fibrillation is safe without transesophageal echocardiography in patients treated with non-vitamin K antagonist oral anticoagulants: Multicenter experience

Abstract: Background: Current guidelines recommend electrical cardioversion (ECV) in patients with atrial fibrillation (AF) after at least 3 weeks of adequate non-vitamin K antagonist oral anticoagulant (NOAC) treatment without prior transesophageal echocardiography (TEE). However, in clinical practice in some centres, TEE is performed before ECV in patients with AF. The aim of the study was to evaluate prevalence of thromboembolic and hemorrhagic complications in patients with AF treated with NOACs and undergoing ECV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Multivariable logistic analysis of clinical data among our 300 patients showed that persistent AF is an independent risk factor for T and SEC4+ with sludge. Several publications indicate the formation of thrombotic material in the heart in both paroxysmal AF and non-paroxysmal AF [22,23,[25][26][27]. Non-paroxysmal AF patients are a heterogeneous group (persistent and permanent AF), and different durations of arrhythmia may have different effects on thrombogenic material formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable logistic analysis of clinical data among our 300 patients showed that persistent AF is an independent risk factor for T and SEC4+ with sludge. Several publications indicate the formation of thrombotic material in the heart in both paroxysmal AF and non-paroxysmal AF [22,23,[25][26][27]. Non-paroxysmal AF patients are a heterogeneous group (persistent and permanent AF), and different durations of arrhythmia may have different effects on thrombogenic material formation.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable logistic analysis revealed that female gender is an independent predictor of thrombogenic milieu formation in LA/LAA. The high CHA2DS2-VASc score, comorbidities including CKD, as well as higher platelet and white blood cell counts found among the female study group are considered to be favorable factors for the formation of thrombogenic material [25,26,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, while TEE has demonstrated utility in detecting LAA thrombi, a well-known risk factor for stroke, a 2021 observational multicenter study observed no evidence of thromboembolic events in patients adequately treated with anticoagulation (apixaban, dabigatran, and rivaroxaban) without pre-procedural TEE [ 29 ]. AFib patients on oral anticoagulation demonstrated a risk of thromboembolism below 1% overall in another study [ 26 ], and anticoagulated patients with thrombi discovered on TEE experienced no embolic events after cardioversion in other studies [ 30 , 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…AFib patients on oral anticoagulation demonstrated a risk of thromboembolism below 1% overall in another study [ 26 ], and anticoagulated patients with thrombi discovered on TEE experienced no embolic events after cardioversion in other studies [ 30 , 31 ]. Despite these findings, there is evidence of the additional utility of TEE before cardioversion in patients with certain risk factors [ 29 ].…”
Section: Reviewmentioning
confidence: 99%